Influence of Ethical Position on Whistleblowing Behaviour: Do Preferred Channels in Private and Public Sectors Differ? - ZAMANTILI NAYIR, DİLEK (SPRINGER, 2018)
Whistleblowing refers to the disclosure by organization members of illegal, immoral, or illegitimate practices to persons or organizations that may be able to effect action. Most studies on the topic have been conducted in North American or European private sector organizations, and less attention has been paid to regions such as Turkey. In this study, we study the whistleblowing intentions and channel choices of Turkish employees in private and public sector organizations. Using data from 327 private sector and 405 public sector employees, we find that public sector employees are more idealistic and less inclined to whistleblow externally and anonymously. Higher idealism among public sector employees does not moderate these effects. We find that private sector employees are more relativistic, and that they are more inclined to whistleblow through external and anonymous channels. More relativistic private sector employees are more likely to prefer external whistleblowing; however sector does not moderate the propensity to whistleblow anonymously.
Keywords: Whistleblowing channels; Private sector; Public sector; Ethical position; PERSONAL MORAL PHILOSOPHIES; DECISION-MAKING; ORGANIZATIONAL CHARACTERISTICS; REPORTING INTENTIONS; UNETHICAL BEHAVIOR; SERVICE MOTIVATION; EMPIRICAL-EVIDENCE; JOB-SATISFACTION; BUSINESS ETHICS; CIVIC ATTITUDES